THE AUDITING LABORATORY AT COLUMBIA UNIVERSITY. - Byrnes, Thomas W. (The Accounting Review, 1935)
Abstract The article focuses on the Auditing Laboratory course offered at Columbia University for the past twenty years. The course prepared for accountancy students, provides a link between the theory and practice of auditing as a business clinic where students might work among the records of actual transactions. A number of sets of used account books form the basis for the course of study which has been given since the spring of 1915. These records present many interesting and complicated problems, and offer a wide scope for analysis and investigation. Questions and problems, to be solved only by an actual examination of these records and books, provide the basis of the student's work. This gives hint a practical working test under conditions which very closely correspond to those met in actual practice. Other problems taken from the actual experience of practitioners are given for home study and solution. These deal not only with auditing practice but also indicate the unusual situations which public accountants are expected to meet.